2021
DOI: 10.1128/msystems.00215-21
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Proteome Analysis of Listeria monocytogenes during Infection Reveals the Role of the AAA+ Chaperone ClpC for Host Cell Adaptation

Abstract: Survival and proliferation of pathogenic bacteria inside the host depend on their ability to adapt to the changing environment. Profiling the underlying changes on the bacterial proteome level during the infection process is important to gain a better understanding of the pathogenesis and the host-dependent adaptation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…In L . monocytogenes and Bacillus subtilis , MurA is a substrate of the ClpCP protease [ 30 , 31 ] and reoM and reoY mutants accumulate MurA to a similar extent as a clpC mutant [ 24 , 27 ]. Analysis of phospho-ablative reoM strains and mutants depleted for PrkA and the corresponding protein phosphatase PrpC showed that genetic constellations, in which ReoM is locked in the phosphorylated state, cause MurA stabilization and vice versa [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In L . monocytogenes and Bacillus subtilis , MurA is a substrate of the ClpCP protease [ 30 , 31 ] and reoM and reoY mutants accumulate MurA to a similar extent as a clpC mutant [ 24 , 27 ]. Analysis of phospho-ablative reoM strains and mutants depleted for PrkA and the corresponding protein phosphatase PrpC showed that genetic constellations, in which ReoM is locked in the phosphorylated state, cause MurA stabilization and vice versa [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein XL-MS and computational modeling has also gained attention for unveiling protein interactions. Early this year Birk et al developed another new method combining metabolic and chemical isobaric peptide labeling to simultaneously determine time-resolved protein decay and de novo synthesis in Listeria monocytogenes ( 85 ). Employing this new method, the authors identified more than 100 ClpC target proteins and observed indirect effects of the clp C deletion on the protein abundance in diverse cellular and metabolic pathways, highlighting the crucial role of ClpC for L. monocytogenes adaptation to the host environment through proteome remodeling.…”
Section: Microorganisms and Their Proteomesmentioning
confidence: 99%
“…And the Liu group also profiled the intracellular proteome of a Salmonella mutant lacking a putative regulatory gene, ydcR , which was found to transcriptionally control the expression of a known virulence factor, SrfN ( 109 ). Other than Salmonella typhimurium, a number of groups also examined the proteome of other bacteria residing within host cells, such as Shigella flexneri ( 110 ), Listeria monocytogenes ( 85 ), Bordetella pertussis ( 111 ), Brucella abortus ( 112 ), and Staphylococcus aureus ( 113 ). Last but not least, there have also been attempts to study bacterial proteomes from in vivo infections ( 93 ), though thus far such practice can still be technically challenging mostly due to limited amounts of sample recovered from infected animal tissues.…”
Section: The Dynamic Host-pathogen Interactions During Infectionmentioning
confidence: 99%
“…The proteomes of many other intracellular bacteria, including S. flexneri , L. monocytogenes , B. pertussis , Brucella ( B .) abortus , R. prowazekii , etc., were also investigated for vaccine development by many groups [ 194 , 195 , 196 , 197 , 198 ]. This research opens the door to the development of a potent vaccine and offers a broad strategy for the design and development of vaccines against other intracellular diseases.…”
Section: Proteomics: a Genomic Complement For Vaccine Developmentmentioning
confidence: 99%